1598. Clinical implications of azole-resistant vs. azole-susceptible invasive aspergillosis in hematological malignancy (CLARITY) – a multicenter study. (31st December 2020) - Seidel, Danila; Cornely, Oliver; Zarrouk, Marouan; Koehler, Philipp; Meis, Jacques F; Salmanton-García, Jon; Vehreschild, Jörg Janne; Christner, Martin; Gräfe, Stefanie K; Falces-Romero, Iker; Lagrou, Katrien; Maertens, Johan; et al.
Abstract: Background: Advances in the survival of patients with invasive aspergillosis (IA) are jeopardized by the emergence of azole resistance in Aspergillus fumigatus, which has been associated with high probability of azole treatment failure. The clinical implications of azole-resistant IA compared to azole-susceptible IA remain unclear. Thus, we seek to describe the epidemiology and to determine the efficacy of antifungal therapy in patients with documented azole-resistant IA compared to azole-susceptible IA in patients with hematological malignancy. Methods: For proven and probable IA (EORTC/MSG 2019) caused by A. fumigatus in patients with hematological malignancies retrospective data were documented, comprising demographics, diagnosis, treatment, response, and outcome. Sites provided susceptibility results or respective isolates for analysis in a central laboratory. Results: Sites in 16 countries worldwide enrolled 187 cases diagnosed with IA between 2010 and 2019; 31 (16.6%) were resistant to at least one of the clinical azoles. Fungal isolates were available from 42 cases. A mixed fungal infection was reported for 32 patients (17.1%), most were related to non- fumigatus Aspergillus and non- Aspergillus molds (n=22, 69%). Most patients were male (66.8%) and overall the majority of patients were in the age groups between 50 and 89 years (71%). Amphotericin B was used for treatment in 24 (77%) patients with azole-resistant IA, compared to 76 (49%) in the azole-susceptible group (lipid-based formulation in 98%); only five (16%) patients with azole-resistant IA were treated with an azole alone vs. 57 (36%) of those with azole-susceptible IA. Overall, all-cause mortality rate was higher for patients with azole-resistant compared to azole-susceptible IA (74.2% vs. 53.8%, log rank P =0.004), the 8 patients with an azole-resistant IA treated in the intensive care unit died within 1 month (Figure 1 ). Details on underlying disease and survival are given in Table 1 . Table 1. Underlying hematological malignancy and clinical outcome of patients with azole-resistant and azole-susceptible invasive aspergillosis Figure 1. Intensive care unit 1-year survival probability for patients with azole-resistant and azole-susceptible invasive aspergillosis Conclusion: Azole-resistance in IA is associated with worse outcome, especially in critically ill patients. Susceptibility testing should be considered in patients with a suspected azole-resistant IA to support treatment decisions. Disclosures: Danila Seidel, PhD, Basilea (Other Financial or Material Support, travel grant) Oliver Cornely, Prof., Actelion (Grant/Research Support)Actelion (Other Financial or Material Support, Personal fees)Al Jazeera Pharmaceuticals (Consultant)Allecra Therapeutics (Other Financial or Material Support, Personal fees)Amplyx (Other Financial or Material Support, Personal fees)Amplyx (Grant/Research Support)Astellas (Grant/Research Support)Astellas (Other Financial or Material Support, Personal fees)Basilea (Other Financial or Material Support, Personal fees)Basilea (Grant/Research Support)Biosys UK Limited (Other Financial or Material Support, Personal fees)Cidara (Other Financial or Material Support, Personal fees)Cidara (Grant/Research Support)Da Volterra (Grant/Research Support)Da Volterra (Other Financial or Material Support, Personal fees)Entasis (Other Financial or Material Support, Personal fees)F2G (Other Financial or Material Support)F2G (Grant/Research Support)Gilead (Grant/Research Support)Gilead (Other Financial or Material Support, Personal fees)Grupo Biotoscana (Other Financial or Material Support, Personal fees)Janssen Pharmaceuticals (Grant/Research Support)Matinas (Other Financial or Material Support, Personal fees)Medicines Company (Grant/Research Support)MedPace (Grant/Research Support)MedPace (Other Financial or Material Support, Personal fees)Melinta Therapeutics (Grant/Research Support)Menarini Ricerche (Other Financial or Material Support, Personal fees)Merck/MSD (Other Financial or Material Support, Personal fees)Merck/MSD (Grant/Research Support)Mylan Pharmaceuticals (Consultant)Nabriva Therapeutics (Other Financial or Material Support, Personal fees)Octapharma (Other Financial or Material Support, Personal fees)Paratek Pharmaceuticals (Other Financial or Material Support, Personal fees)Pfizer (Other Financial or Material Support, Personal fees)Pfizer (Grant/Research Support)PSI (Other Financial or Material Support, Personal fees)Rempex (Other Financial or Material Support, Personal fees)Roche Diagnostics (Other Financial or Material Support, Personal fees)Scynexis (Other Financial or Material Support, Personal fees)Scynexis (Grant/Research Support)Seres Therapeutics (Other Financial or Material Support, Personal fees)Tetraphase (Other Financial or Material Support, Personal fees) Philipp Koehler, MD, Akademie für Infektionsmedizin e.V., (Other Financial or Material Support, Personal fees)Astellas Pharma GmbH (Other Financial or Material Support, Personal fees)Cologne Excellence Cluster on Cellular Stress Responses in Aging-Associated Diseases, University of Cologne, Cologne, Germany (Other Financial or Material Support, Other)Gilead Sciences GmbH (Other Financial or Material Support, Personal fees)GPR Academy Ruesselsheim (Speaker's Bureau)Miltenyi Biotec GmbH (Other Financial or Material Support, Non-financial support)MSD Sharp & Dohme GmbH (Other Financial or Material Support, Personal fees)Noxxon N.V. (Speaker's Bureau)University Hospital, LMU Munich (Other Financial or Material Support, Personal fees) Katrien Lagrou, n/a, FUJIFILM WAKO (Speaker's Bureau)Gilead (Consultant, Speaker's Bureau)MSD (Consultant, Speaker's Bureau, Other Financial or Material Support, travel grant)Pfizer (Speaker's Bureau, travel grant)SMB Laboratoires Brussels (Consultant) Zdenek Racil, n/a, Astellas (Grant/Research Support, Speaker's Bureau, travel grant) Blandine Rammaert, n/a, Gilead (Speaker's Bureau, Other Financial or Material Support, travel grant)Merck/MSD (Speaker's Bureau)Pfizer (Other Financial or Material Support, travel grant) Nikolay Klimko, n/a, Astellas (Speaker's Bureau)Gilead (Speaker's Bureau)Merck/MSD (Speaker's Bureau)Pfizer (Speaker's Bureau) Sung-Yeon Cho, MD, Gilead (Grant/Research Support, Speaker's Bureau)Merck Sharp & Dohme (Grant/Research Support, Speaker's Bureau)Pfizer (Grant/Research Support, Speaker's Bureau)